Stepping outside the consultation room. On nurse–patient relationships and nursing responsibilities during a type 2 diabetes walking project. (6th June 2019) - Stuij, Mirjam; Elling‐Machartzki, Agnes; Abma, Tineke A.
Abstract: Aims: To examine the care practices of nurses during the organization of 20 weeks of walking sessions for people with type 2 diabetes and to reflect on implications for nurse–patient relationships and nursing responsibilities in the provision of physical activity (PA) care. Design: Qualitative, ethnographic study. Methods: Almost 70 hr of field work was completed by participant observations and informal conversations with nurses and participating patients of two different walking groups (April–October 2016). Analysis of field notes followed an inductive holistic‐content approach, using both within‐case and across‐case analysis. Results: The analysis revealed four main themes related to the nurses' care practices: (a) organizational efforts; (b) combining group and individual care; (c) stepping in‐ and outside the patient mode; and (d) implications back inside the consultation room. Underlying these themes was a process of relational development, both with and among patients. Conclusion: Stepping outside the consultation room seems to offer more space for patients' lifeworld narratives and contribute to more continuous and person‐centred care. However, it also raises new questions about the provision of PA care and nursing responsibilities in this. Impact: Current nursing repertoires for PA counselling in type 2 diabetes care are insufficient and might be extended by organizing walking sessions for patients. Related nursing care practices impacted relationships both with and among participating patients. These have consequences for boundaries of both nursing responsibilities and care provision. Abstract : 目的: 研究护士在为2型糖尿病患者组织为期20周的步行项目期间的护理实践, 并反思在提供身体活动(PA)护理中对护患关系和护理职责的影响。 设计: 定性、人类学研究。 方法: 通过参与者观察和与两个不同步行组的护士和参与患者的非正式谈话(2016年4月至10月), 完成了近70小时的现场工作。现场笔记的分析遵循归纳的整体内容方法, 使用案例内和跨案例分析。 结果: 分析揭示了与护士护理实践相关的四个主要主题:(a)组织工作;(b)将集体和个人护理结合起来;(c)走入和走出患者模式;以及(d)回到诊察室的启示。在这些主题的基础上是一个关系发展的过程, 无论是与患者之间还是与患者之间。 结论: 走出诊察室似乎为患者的生活世界叙述提供了更多的空间, 并有助于更加持续和以人为中心的护理。然而, 这也提出了关于提供身体活动护理和护理责任的新问题。 影响: 目前2型糖尿病护理中身体活动咨询的护理计划不足, 可以通过为患者组织步行项目来延长。相关的护理实践影响了和参与患者以及患者之间的关系。这些都会影响到护理责任和护理规定的界限。